Medical Students Perceptions about Fieldlab Role in Achieving Communication Competencies - Prisma Putra Ghirby Aseptama; Eti Poncorini Pamungkasari; Anik Lestari (Nexus Pendidikan Kedokteran dan Kesehatan, 2017)
Introduction: Communication is one of the basic competence of a medical doctor. Community-based education as one of the educational methode in medical curriculum has a role to achieve communication competence and the other medical doctor competencies. Fieldlab is a learning program that using community-based education methode. The purpose of this study is to know how the role of fieldlab on achieving medical doctor competencies at communication aspect. Methods: This study was a qualitative study with a purposive sampling method. The sample was medical students of faculty of medicine, Sebelas Maret University batch 2012 that has pass all topics of fieldlab. The metode of collecting data was using 4 group of focus group discussion (FGD) with 6 to 8 subject in each group. This study analyzed with content analysis technique. Results: This study found some fieldlab roles in achieving medical doctor competencies in communication aspect. Such as train the ability to communicate to the community, inter-profession communication, and communication with patients. Otherwise, it found that there were things could hinder the communication competencies achievement. Conclusions: Fieldlab has role to increasing the doctor competence in communication aspect of medical student. Keywords: fieldlab, community-based education, communication, competency